Introduzione (ENTHYMEMA, 2012)
Seen from today, the Seventies seem inscribed in a paradox. On the one hand, they don‘t pose problems of periodization, being unanimously identified with the span of years between 1968 and 1980, with an almost perfectly overlapping chronology in Europe and the U.S. On the other hand, however, the temporal frame marking out the decade as different from what came before (the Sixties) and after (the Eighties) does not coincide to any conceptual closure. Instead, the safe chronological enclosure is disrupted by the con-ceptual field of forces, play of ideas, social tensions that did define the experience of the Seventies but were not contained, resolved or exhausted within its temporal frame. This special section of Enthymema presents a first, tentative reconnaissance of what has re-mained that decade in contemporary poetics and theoretical discourse.